A Qualitative Study of Women’s Lived Experiences of Conflict and Domestic Violence in Afghanistan - Mannell, Jenevieve (Violence against women, 2021)
This article empirically explores women’s lived experiences of domestic violence and conflict in Afghanistan. A thematic analysis of 20 semistructured interviews with women living in safe houses produced three main themes about the relationship between conflict and domestic violence: (a) violence from loss of patriarchal support, (b) violence from the drug trade as an economic driver, and (c) violence from conflict-related poverty. We discuss the bidirectional nature of this relationship: Not only does conflict contribute to domestic violence, but domestic violence contributes to conflict through justifying armed intervention, separating women from economic and public life, and perpetuating patriarchy.